Global governance in the age of epistemic authority. Issue 1 (28th March 2021) - Pouliot, Vincent
Abstract: Today's global governance is qualitatively different from the past, according to Michael Zürn's penetrating analysis. With the rise of epistemic authority, reflexivity, service, and request have come to surpass command and control as key modes of global governance, leading to new forms of legitimation and contestation. I engage with this rich and thought-provoking argument on three counts. First, it remains doubtful that states defer to international organizations because the latter 'know better'. There exist many gaps in epistemic authority and politics often trump rationality in global governance. Second, it is not clear how global hierarchy, which Zürn equates with 'pockets of authority', could emerge out of demands and requests, precisely because epistemic authority is so fluid and prone to contestation. Third, as historically young and increasingly based on service authority as it may be, contemporary global governance still rests on a body of inherited practices whose legitimation principles seem closer to tradition than to reflexive justification.